Structural hemodynamic valve deterioration durability of RESILIA-tissue versus contemporary aortic bioprostheses - Krzysztof Bartus; Joseph E Bavaria; Vinod H Thourani; Ke Xu; Eric L Keuffel (Becaris Publishing Limited, 2023)
Aim: Durability of aortic valve replacement is becoming increasingly important. Aortic bioprostheses with RESILIA tissue have demonstrated outstanding outcomes thus far, but only in single-arm studies. Methods: We compared structural valve deterioration (SVD)-related hemodynamic valve deterioration (HVD) of grade ≥2 of RESILIA tissue valves from the COMMENCE trial (n = 689) to those from the PARTNER 2A contemporary AVR arm (n = 936) based upon annual core laboratory echocardiograms through 5 years of follow-up. Results: SVD-related HVD in the COMMENCE and PARTNER 2A cohorts were 1.8 versus 3.5%, respectively (one-sided 95% lower-bound hazard ratio of 0.92; p = 0.07). In propensity-matched cohorts (n = 239), these outcomes were 1.0 versus 4.8%, respectively (one-sided 95% lower-bound hazard ratio of 1.15; p = 0.03). Conclusion: RESILIA tissue-based AVR exhibited reduced SVD-related HVD compared with a contemporary AVR cohort devoid of RESILIA tissue.